2011
DOI: 10.1080/00223891.2011.594133
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Attachment Projective Picture System: Integrating Attachment Into Clinical Assessment

Abstract: This article summarizes the development and validation of the Adult Attachment Projective System (AAP), a measure we developed from the Bowlby-Ainsworth developmental tradition to assess adult attachment status. The AAP has demonstrated excellent concurrent validity with the Adult Attachment Interview (George, Kaplan, & Main, 1984/1985/1996; Main & Goldwyn, 1985-1994; Main, Goldwyn, & Hesse, 2003), interjudge reliability, and test-retest reliability, with no effects of verbal intelligence or social desirabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
391
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(402 citation statements)
references
References 46 publications
(56 reference statements)
7
391
1
3
Order By: Relevance
“…Moreover, these colleagues also suggested that he reflect on the parents' childhood histories of parenting as their tacit practice knowledge signalled that losses sustained in early childhood may contribute to later emotional difficulties encountered in parenting. Subsequent research on adult attachment has established that unresolved emotional experience in childhood (e.g., loss) is regularly associated with attachment insecurity in adults (George & West, 2011). This finding confirms the social workers' early, practice-based conceptualisations.…”
Section: Original Article the Impact Of Childhood Losssupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, these colleagues also suggested that he reflect on the parents' childhood histories of parenting as their tacit practice knowledge signalled that losses sustained in early childhood may contribute to later emotional difficulties encountered in parenting. Subsequent research on adult attachment has established that unresolved emotional experience in childhood (e.g., loss) is regularly associated with attachment insecurity in adults (George & West, 2011). This finding confirms the social workers' early, practice-based conceptualisations.…”
Section: Original Article the Impact Of Childhood Losssupporting
confidence: 77%
“…The relational state of most concern, specifically from a care practice perspective, involves adult experiences of unresolved trauma and loss. Adults operating from this stance have been described as frightening and disorienting to children because their shift in mind states can be rapid and unpredictable (George & West, 2011). These mind states are narratively displayed through momentary lapses in reasoning.…”
Section: Original Articlementioning
confidence: 99%
“…1988). Following this emphasis, some attachment theorists have used segregated systems as the basis for their thinking and design of attachment measures, such as George and West’s (2012) Adult Attachment Projective , which uses segregated systems as the theoretical basis for the adult attachment classification equivalent of disorganization. Despite its clear importance for his thinking, however, Bowlby offered little published discussion of the concept of segregated systems.…”
Section: Bowlby’s Theory: Segregated Systemsmentioning
confidence: 99%
“…Basically, I propose that tests like the Rorschach (Exner, 2003), Thematic Apperception Test (TAT; Murray, 1943), Adult Attachment Projective Picture System (AAP; George & West, 2012), and others-because of their visual, emotionally arousing stimulus properties and the emotionally arousing aspects of their administration procedures-tap into material that is more reflective of right-hemisphere and subcortical functioning. Other tests like the Minnesota Multiphasic Personality Inventory (MMPI-2; Butcher et al, 2001), Beck Depression Inventory (BDI; Beck, Ward, Mendelson, Mock, & Erbaugh, 1961), and Symptom Checklist-90-R (SCL-90-R; Derogatis & Savitz, 2000) utilize more left-hemisphere cortical functions because of their verbal format and nonemotionally arousing adminstration.…”
Section: The Importance Of Performance-based Personality Testsmentioning
confidence: 99%